Trigeminal and dorsal root ganglion neurons express CCK receptor binding sites in the rat, rabbit, and monkey: possible site of opiate- CCK analgesic interactions - Ghilardi, JR (J Neurosci, 1992)
125I-Bolton-Hunter sulfated cholecystokinin-8 was used to localize and characterize cholecystokinin (CCK) receptor binding sites in trigeminal and dorsal root ganglia, and in the spinal cord of the rat, rabbit, and monkey. In the rabbit and monkey, a substantial number, 90 +/- 21% and 24 +/- 8%, respectively, of trigeminal and dorsal root ganglion neurons express CCK binding sites. In the spinal cord, the highest concentration of CCK receptors is found in laminae I and II, which is the major termination site of dorsal root ganglia neurons expressing CCK receptor binding sites. Neonatal capsaicin treatment of the rat results in a 70% decline in CCK receptor binding sites in laminae I and II of the spinal cord, indicating that dorsal root ganglia neurons are a major source of CCK receptors in the spinal cord. Pharmacological experiments using selective CCK-A and CCK-B receptor antagonists demonstrate that CCK-B is the prominent CCK receptor subtype in trigeminal and dorsal root ganglia neurons in the rat, rabbit, and monkey. In the rat and rabbit spinal cord, CCK-B binding sites are the prominent subtype, whereas in the monkey cord, CCK-A is the prominent receptor subtype. These results demonstrate that CCK-B receptors are expressed by a substantial percentage of dorsal root ganglion neurons at all spinal levels, and that CCK may antagonize opiate analgesia at the level of the primary afferent neuron itself.